Dispersion of complex carbides at the oxidation front during the oxidation of 9Cr-1Mo steel. (1st April 2020) - Coghlan, L.; Yan, S.; Shin, Aya; Pearson, J.; Jepson, M.A.E; Higginson, R.L.
Graphical abstract: Highlights: Multi-elemental complex carbides develop in 9Cr-1Mo steel exposed to CO2 . Both M7 C3 and M23 C6 have been identified in a multi-component carbide. Most carbides oxidize upon exposure to the oxidation front forming an IOZ. Certain carbides resist oxidation through the growth of a Cr rich oxide shell. Abstract: To better understand oxidation and carburisation processes taking place during exposure of 9Cr-1Mo steel experimental samples have been exposed at 600 °C and 620 °C to a CO2 rich atmosphere for various exposure times. Complex multi-elemental carbides form showing a range of compositions, with some showing coring/elemental segregation. Certain carbides show both M7 C3 and M23 C6 within a single multi-component carbide. At the oxidation front some carbides resist oxidation through growth of a Cr rich oxide shell. Carbides within both substrate and oxide have been characterized with mechanisms being proposed for the complex interactions taking place within both the substrate and oxide.